LIABILITY AND COMPLETION OF THE LAW ON NOTARY DEED ARE MADE NURSING HIS RULE - Ristya Putri Asriyani; Gunarto Gunarto (Sultan Agung Notary Law Review, 2020)
Issues raised in this study first, how a form of accountability notary who has ended his tenure on the deed he made before the end of his tenure? Second, how the legal protection of a notary who has ended his tenure on the deed made before nursing. This study analyzed qualitatively in the form of research reports, descriptive and approach of this research is the approach of legislation and case-based approach to the type of juridical empirical research. From the analysis of the study concluded that the first form of responsibility notary who has ended his tenure against the violation of the law office of a notary, may be accounted for either administrative, civil and criminal as well as a variety of sanctions. Second,Keywords: Notary nursing; responsibilities of a notary; notary legal protection